Self-Legitimacy of Prison Workers and Treatment of Correctional Clients: A Study in Slovenian Prisons - Hacin, Rok (Criminal justice and behavior, 2024)
Studies on self-legitimacy in the prison environment have confirmed the differences in prison workers’ perceptions of their own legitimacy in different cultural settings. This study focuses on factors influencing prison workers’ self-legitimacy and their support of the specific treatment of correctional clients in Slovenian prisons. The results highlighted good relations with correctional clients, satisfaction with payment, internalization of subcultural norms, higher education, and positive perception of workplace (professional) competencies as correlates of prison workers’ self-legitimacy. Prison workers’ support of the resocialization of correctional clients was influenced by their feelings of obligation toward correctional clients, rejection of prison subculture norms, and gender, female prison workers being more inclined toward resocialization. In contrast, lack of cooperation between prison services, bad relations with correctional clients, and lower levels of achieved education were associated with prison workers’ support of the harsh treatment of correctional clients. The implications of these findings are discussed.